Pembelajaran Bahasa Inggris melalui Siaran Radio Komunitas Balai Budaya Minomartani FM 107.7 MHz - Sharifah Hanidar; Rio Rini Diah Moehkardi (Faculty of Cultural Sciences, 2019)
The community service program conducted by the English Study Program held from April to July, 2019 was the fourth in a series of activities in cooperation with Balai Budaya Minomartani and the community radio station, Balai Budaya Minomartani FM 107.7 MHz. It aims to increase the community capacity by training high school students living in Minomartani and its vicinity to become broadcasters of an educational entertainment radio program. In this program, Indonesian folktales in English translation are used as a medium for teaching English through storytelling. In achieving the aim, a two day workshop on radio broadcasting was held at the Faculty of Cultural Sciences, Universitas Gadjah Mada. The resource persons presenting in the workshop are community radio practitioners from the community radio station and lecturers from the English Study Program, Universitas Gadjah Mada. In the workshop, participants learned how to operate audio mixer, tell stories and present material on the radio. The participants were also provided with a module to help them identify language items to teach and select, modify, and convert the folk tales into audio scripts. Under the guidance and supervision of tutors from the English Study Program, the participants selected the language items in the folktales and developed them into teaching materials, made audio scripts and presented them. The participants were recorded reading their scripts. The audio recording was then broadcasted by the community radio station, Balai Budaya Minomartani FM 107.7 MHz. As the community radio is internet-based, the broadcast could be heard world wide. In this way, Indonesian folktales are also promoted to the world.————————————————————–Pengabdian kepada Masyarakat yang dilaksanakan Prodi Sastra Inggris sejak April–Juli 2019 bekerja sama dengan Balai Budaya Minomartani dan Radio Komunitas Balai Budaya Minomartani FM 107.7 MHz, merupakan yang keempat kalinya dalam serangkaian kegiatan kerjasama. Pengabdian kepada Masyarakat ini bertujuan mengembangkan kapasitas masyarakat dengan melatih siswa SMA/SMK yang tinggal di Minomartani dan sekitarnya untuk menjadi penyiar program pendidikan dan hiburan. Dalam program ini, cerita rakyat Indonesia yang telah diterjemahkan ke dalam bahasa Inggris digunakan sebagai media pembelajaran bahasa Inggris dengan memakai metode storytelling. Untuk mencapai tujuannya, Prodi Sastra Inggris menyelenggarakan workshop yang berlangsung selama dua hari di Fakultas Ilmu Budaya, Universitas Gadjah Mada. Para narasumber merupakan praktisi radio komunitas dan dosen dosen Prodi Sastra Inggris, Universitas Gadjah Mada. Para peserta workshop diajarkan bagaimana mengoperasikan audiomixer, bercerita dan menyiarkan materi. Di samping itu, para peserta diberikan modul untuk membantu mereka dalam mengidentifikasi butir bahasa yang akan diajarkan, memilih, memodifikasi dan mengubah cerita rakyat menjadi audio script. Di bawah bimbingan tutor dari Prodi Sastra Inggris, peserta memilih unsur bahasa yang terdapat dalam cerita rakyat dan mengembangkannya menjadi bahan ajar, membuat audio script, membacakannya sambil direkam untuk kemudian disiarkan di radio komunitas Balai Budaya Minomartani FM 107.7 MHz. Karena radio komunitas BBM sudah berbasis internet, siaran ini dapat didengarkan di seluruh dunia sehingga menjadi sarana promosi cerita rakyat Indonesia.